(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
Objective: To find out the frequency of consanguinity and positive family history of hearing impairment among deaf children in a deaf school in Bangladesh. Methods: This was a retrospective study were included 150 patients. They were subjected to complete audiological examinations. These pupils were collected from Integrated Pre-school for Hearing Impaired children (IPSHIC) of SAHIC, Mohakhali, Dhaka, Bangladesh. Results: The results showed that out of 150 Hearing impaired (HI ) children 30.0% (45) were from the consanguineous parents and 70.0% (105) from non- consanguineous parents. Also found 22.0% (33) had positive family history of hearing impairment. Conclusion: Prevention is only means to reduce the prevalence of Congenital hearing impairment. DOI: http://dx.doi.org/10.3329/bjo.v20i2.22020 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 60-65